Pengaruh Kompetensi Paedagogik Guru Terhadap Prestasi Belajar Siswa Kelas XI Mata Pelajaran PAI Di SMKN 13 Malang - admin admin; Subhan Adi Santoso (TAMADDUN : Jurnal Pendidikan dan Pemikiran Keagamaan, 2017)
Pedagogic competence is the ability to manage student learning which includes students 'understanding, design and implementation of learning, evaluation of learning outcomes, and development of students to develop various potentials of students, while learning achievement is the aspect of the students' skills as a result of business and learning activities pursued, Is seen as an important indicator in the overall process of education in general and the process of teaching and learning in particular. The method used in data collection is descriptive method. While the approach taken is a quantitative approach. Data collection in this study includes literature study and field study. The implementation of this field study involves observation techniques, interviews, and using data collection instruments in the form of questionnaires. The average score of teacher paedagogic competency variables (Variable X) has an average of 2.49, the scores in the assessment criteria are at 2.5-3.5 intervals with medium qualifications and for the average grade of learning achievement Students (Variable Y) that has an average value of 3.67 numbers in the scale of the assessment is at the interval of 3.5-4.5 with high qualification. Based on data analysis there is a significant relationship between teacher Paedagogic Competence on student achievement. The magnitude of the effect of variable X to Y is 0.86. The contribution of variable X to Y is 49% and the remaining 51% is influenced by other factors .. This information provides information that the teacher paedagogic competence variables have a strong influence on student achievement that is Based on the above calculation known that the value of Z arithmetic 4.3> Z table 0.01 then the hypothesis (Ho) rejected and (Ha) accepted, this means the influence between variable X and variable Y with significant influence.